Portrait, self-portrait and identity in early childhood education - Moreno Vera, Juan Ramón (2016)
The research makes a didactic experience during Early-Childhood education where the students work around self and others identity trought the arts, specifically portraiture and self-portraiture. This genre permits to represent the human figure, its attributes, and the emotions or personal relationships that the students identify. The didactic experience was developed in five schools in Alicante province (Spain) in Early-childhood classrooms. The results shows the capacity of the students to recognize the parts of the body, to represent them on their own or on the others, and as well to show the emotions or personal relationship that are present in their lifes.